2021
DOI: 10.3390/antibiotics10121534
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Lysozyme, an Innate Immune Defense Factor, as an Alternative Antibiotic

Abstract: Lysozyme is a ~14 kDa protein present in many mucosal secretions (tears, saliva, and mucus) and tissues of animals and plants, and plays an important role in the innate immunity, providing protection against bacteria, viruses, and fungi. Three main different types of lysozymes are known: the c-type (chicken or conventional type), the g-type (goose type), and the i-type (invertebrate type). It has long been the subject of several applications due to its antimicrobial properties. The problem of antibiotic resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
92
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(125 citation statements)
references
References 336 publications
1
92
0
Order By: Relevance
“…Thus, this may explain why lysozyme can more easily hydrolyze the wall of S. epidermidis 444 in comparison to L. rhamnosus GG. Moreover, several previous studies have demonstrated the ability of lysozyme to prevent biofilm formation (Leitch and Willcox 1999 ; Ferraboschi and Ciceri 2021 ). Hence, a concentration of 30 μg/mL was able to decrease the biofilm-forming capacities of a wide spectrum of hospital and reference strains of microorganisms such as Gardnerella vaginalis , Staphylococcus aureus , Staphylococcus epidermidis and Pseudomonas aeruginosa (Hukić et al 2018 ).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Thus, this may explain why lysozyme can more easily hydrolyze the wall of S. epidermidis 444 in comparison to L. rhamnosus GG. Moreover, several previous studies have demonstrated the ability of lysozyme to prevent biofilm formation (Leitch and Willcox 1999 ; Ferraboschi and Ciceri 2021 ). Hence, a concentration of 30 μg/mL was able to decrease the biofilm-forming capacities of a wide spectrum of hospital and reference strains of microorganisms such as Gardnerella vaginalis , Staphylococcus aureus , Staphylococcus epidermidis and Pseudomonas aeruginosa (Hukić et al 2018 ).…”
Section: Discussionmentioning
confidence: 97%
“…The obtained results were in accordance with other studies revealing that L. rhamnosus GG and S. epidermidis 444 can survive in a harsh environment. Thus, they can resist pH values as low as 2.5 but with a low survival rate and poor proliferative capacity (Nishiyama et al 2016 ; Ferraboschi and Ciceri 2021 ). Therefore, this may justify the decrease in the survival rate in the stomach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HEWL is a potential alternative to antibiotics: however, it is difficult to express in microbial expression systems in large quantity, which greatly limits its application [ 29 ]. To date, heterologous expression of HEWL has been attempted in microbial expression systems, but low expression levels are still a problem and an issue to be solved.…”
Section: Discussionmentioning
confidence: 99%
“…OLFM4 is then involved in the destruction of the intestine. Clinical research is focusing on the role of LYZ as a potential biomarker in feces and blood of intestinal inflammatory diseases [ 33 ] and its medical application, using the protein’s anti-inflammatory, anti-bacterial and immunomodulating effects in gastroenterological diseases [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%